Preliminary investigation and interview guide development for studying how Malaysia farmers' form their mental models of farming - Steven, Eric Krauss; Hamzah, Azimi; Omar, Zoharah; Suandi, Turiman; Ismail, Ismi Arif; Zahari, Mohd Zaidan; Mohd Nor, Zanariah (The Qualitative Report, 2009)
The development of the interview guide is an integral aspect of the process of conducting qualitative research, yet one that receives little attention in the qualitative research literature. It is often assumed that interview guides are merely a list of questions used to guide a qualitative interview. The background analysis and preparation necessary to prepare an appropriate and effective guide cannot be dismissed, however, as they are integral aspects of the interview process. The current study on mental models of Malaysian smallholder farmers employed in-depth interviews as its primary approach to data generation. This paper details the initial processes undertaken to develop the interview guide based on preliminary data generation. The results included seven main steps to interview guide development.